2014
DOI: 10.1002/adem.201400045
|View full text |Cite
|
Sign up to set email alerts
|

Strain‐Induced Alignment Mechanisms of Carbon Nanotube Networks

Abstract: Random networks comprised of millimeter-long multi-walled carbon nanotubes (CNTs) have shown unique microstructure change mechanisms under uniaxial strain. These networks can be modified into highly aligned microstructures from strain-induced plastic deformation. Applying a treatment consisting of an uncured resin as a load transfer enhancement medium leads to a dramatically increased degree of alignment and final mechanical properties of the CNT networks. The structural evolution of the CNT networks includes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 17 publications
2
46
0
Order By: Relevance
“…Currently, the mechanical-strain-induced strategy mainly focuses on the preparation of ordered structures of 1D nanotubes and 2D nanosheets within hydrogel matrixes, and these reported nanocomposite hydrogel materials exhibit anisotropic optical and mechanical performances. [81][82][83][84][85][86] Under tensile strain, polyacrylamide chains and 1D imogolite nanotubes in hydrogels were aligned, resulting in the formation of aligned internal structures (Figure 5a). [81,82] The obtained nanocomposite hydrogels, which had aligned structures, displayed strongly anisotropic mechanical/optical behaviors.…”
Section: Mechanical Strainmentioning
confidence: 99%
“…Currently, the mechanical-strain-induced strategy mainly focuses on the preparation of ordered structures of 1D nanotubes and 2D nanosheets within hydrogel matrixes, and these reported nanocomposite hydrogel materials exhibit anisotropic optical and mechanical performances. [81][82][83][84][85][86] Under tensile strain, polyacrylamide chains and 1D imogolite nanotubes in hydrogels were aligned, resulting in the formation of aligned internal structures (Figure 5a). [81,82] The obtained nanocomposite hydrogels, which had aligned structures, displayed strongly anisotropic mechanical/optical behaviors.…”
Section: Mechanical Strainmentioning
confidence: 99%
“…In this study, it was not possible to apply strains greater than ~15% without breaking the veils. Higher strains have been reported using a variety of methods [4,18], but the maximum is likely dependent on the initial orientation of the veil, and other processing factors such as rate and lubrication. Here, different strains are applied simply to demonstrate the analysis method, although in the medium term, the approach should help to optimise the drawing process.…”
Section: Cnt Veil Orientation Measurement and Validationmentioning
confidence: 89%
“…Aligning carbon nanotubes within such preformed arrays can improve mechanical [4,5,6,7], thermal [8,9,10,11] and electrical [12,13,14] properties. A number of studies have shown an linear increase in tensile modulus and strength with an increase in orientation ( Figure 1).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…The material is now available in commercial quantities of sheets and yarns [11] with mechanical properties that support their use as structural reinforcement [12][13][14][15][16][17], and electrical conductivity sufficient for data cables [18]. Spun yarns with good mechanical properties have also been shown to carry useful levels of current [19].…”
Section: Introductionmentioning
confidence: 99%